Super-flexible bis(trifluoromethanesulfonyl)-amide doped graphene transparent conductive electrodes for photo-stable perovskite solar cells. Issue 18 (26th April 2018) - Heo, Jin Hyuck; Shin, Dong Hee; Song, Dae Ho; Kim, Do Hun; Lee, Sang Jin; Im, Sang Hyuk
Abstract : Super-flexible bis(trifluoromethanesulfonyl)-amide (TFSA)-doped graphene transparent conducting electrode (GR TCE)-based FAPbI3 − x Br x perovskite solar cells with 18.9% power conversion efficiency (PCE) for a rigid device and 18.3% for a flexible one are demonstrated because the TFSA-doped GR TCE reveals high conductivity and high transmittance. Abstract : Super-flexible bis(trifluoromethanesulfonyl)-amide (TFSA)-doped graphene transparent conducting electrode (GR TCE)-based FAPbI3 − x Br x perovskite solar cells with 18.9% power conversion efficiency (PCE) for a rigid device and 18.3% for a flexible one are demonstrated because the TFSA-doped GR TCE reveals high conductivity and high transmittance. The unencapsulated TFSA-doped GR TCE-based cell maintained ∼95% of its initial PCE under a continuous light soaking of 1 Sun at 60 °C/30% relative humidity for 1000 h. In addition, the TFSA-doped GR TCE-based flexible perovskite solar cells show excellent bending stabilities, maintaining PCEs of ∼85, ∼75, and ∼35% of their original values after 5000 bending cycles, at R = 12, 8, and 4 mm, respectively.